2013
DOI: 10.1016/j.juro.2012.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Obesity and Risk of High Grade Disease in Clinical T1a Renal Cell Carcinoma

Abstract: Increased visceral obesity was found to be strongly associated with higher Fuhrman grade in patients with cT1a renal cell carcinoma. Further studies are needed to confirm these findings and discover the underlying biological mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 28 publications
5
50
0
Order By: Relevance
“…Furthermore, regardless of BMI, women appear to have higher levels of SFA and fat mass than men. 8,10,16,17,28 Similarly, in the current study the correlation between BMI and VFA (r = 0.542) was relatively weak when compared to that of BMI and SFA (r = 0.804) and BMI and TFA (r = 0.846). In addition, women had higher SFA but lower VFA than men, but did not differ from men with regard to BMI or TFA.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Furthermore, regardless of BMI, women appear to have higher levels of SFA and fat mass than men. 8,10,16,17,28 Similarly, in the current study the correlation between BMI and VFA (r = 0.542) was relatively weak when compared to that of BMI and SFA (r = 0.804) and BMI and TFA (r = 0.846). In addition, women had higher SFA but lower VFA than men, but did not differ from men with regard to BMI or TFA.…”
Section: Discussionsupporting
confidence: 49%
“…Unlike previous reports, they demonstrated that high VFA% was associated with a higher grade of RCC. 17 Two previous studies evaluated the predictive value of visceral adiposity in metastatic RCC patients treated with anti-angiogenic therapy, reporting contradicting results. While one study showed that higher than median VFA values were significantly associated with a shorter progression-free survival and OS, the other demonstrated an opposite correlation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results point out a possible association between MetS and tumor carsinogenesis, eventhough we did not confirm any link either between MetS and nuclear grade or between MetS and RCC subtype. In another study, increased visceral obesity, a key component of MetS, was found to be strongly associated with higher Fuhrman grade in patients with clinical T1a RCC (Zhu et al, 2013). Since our results reflect the experience of a single institution, our study cohort may not have analogous regional or individual risk factors contributing to tumor aggressiveness or subtype formation with abovementioned studies.…”
Section: Discussionmentioning
confidence: 48%
“…Zhu et al recently reported on a series of 186 patients with surgically treated T1a RCC. 17 They found significant relationships between the percentages of visceral adipose tissue and tumor size with higher Fuhrman grades. Similar to our findings, multivariate analysis showed that the percentages of visceral adipose tissue (OR 1.06, p = 0.0018) and tumor size (OR 1.91, p = 0.047) were independent predictors of high-grade cancer.…”
Section: Discussionmentioning
confidence: 97%